A novel amelogenesis-inspired hydrogel composite for the remineralization of enamel non-cavitated lesions. Issue 48 (6th December 2022) - Liu, Zhenqi; Lu, Junzhuo; Chen, Xiangshu; Xiu, Peng; Zhang, Yinmo; Lv, Xiaohui; Jiang, Xinyi; Wang, Kun; Zhang, Linglin
Abstract : Biomimetic design strategy of BQ hydrogel composite and its remineralizing effect on enamel NCLs. Abstract : Enamel non-cavitated lesions (NCLs) are subsurface enamel porosity from carious demineralization. The developed enamel cannot repair itself once NCLs occurs. The regeneration of mineral crystals in a biomimetic environment is an effective way to repair enamel subsurface defects. Previously, an amelogenin-derived peptide named QP5 was proven to repair demineralized enamel. In this work, inspired by amelogenesis, a novel biomimetic hydrogel composite containing the QP5 peptide and bioactive glass (BG) was designed, in which QP5 could promote enamel remineralization by guiding the calcium and phosphorus ions provided by BG. Also, BG could adjust the mineralization micro-environment to alkalinity, simulating the pH regulation of ameloblasts during enamel maturity. The BQ hydrogel composite showed biosafety and possessed capacity for enamel binding, ion release and pH buffering. Enamel NCLs treated with the BQ hydrogel composite showed a higher reduction in lesion depth and mineral loss both in vitro and in vivo . Moreover, compared to the hydrogels containing only BG or QP5, groups treated with the BQ hydrogel composite attained more surface microhardness recovery and color recovery, exhibiting resistance to erosion and abrasion of the remineralization layer. We envision that the BQ hydrogel composite can provide a biomimetic micro-environment to favor enamel remineralization, thus reducing the lesion depth and increasing the mineral content as a promising biomimetic material for enamel NCLs.